Effects of fatigue on kinetic parameters during a simulated cross-country ski race. Preliminary results - Pellegrini, B.; Bortolan, L.; Fabre, N.; Schena, F. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Fatigue is defined as a decrease in performance or in work capacity or as the inability to maintain a level of strength. Very few studies have analyzed the effect of fatigue on the technique in cross-country skiing in an ecological setting (on-field). The purpose of the study was to examine the changes induced by fatigue on kinematic parameters and force expression during a race simulation using diagonal stride technique. Methods Eight cross-country skiers were asked to complete a 12-km simulated race, consisting of 8 laps of 1.5 km each using classical style technique. The subjects were timed over each lap and passage along a straight and constant uphill tract (length: 130m, slope: 12%) that was covered using diagonal stride. The athletes were filmed over a field of 8m at the end of the uphill tract by means of 3D SIMI motion system. Length and duration of the cycle (CL; CT), of the gliding phase (GL; GT) and the duration of the propulsive phase (PT) were calculated. The plantar and the pole forces were recorded over the whole simulation using a Novel Pedar System and load cells inserted under the handgrips. Mean force, peak force and duration of the propulsive phase were considered for both skis and poles during uphill tract. Blood lactate concentration was measured at each lap. Mean parameter of the first lap (L1) and last lap (LL) were compared. Results Preliminary analysis on the first two skiers (S1 and S2) indicated a reduction of the speed (S1:2.89m/s for L1, 2.68m/s for LL; S2: 2.98m/s for L1, 2.59m/s for LL) on the uphill tract. The mean value for lactate concentration was 7.5mmol/l and no values below 6mmol/l were found. Temporal variables showed a slight decrement of the GT (S1:0.29s for L1, 0.26s for LL; S2:0.25s for L1, 0.21s for LL) associated to a reduction of the CL (S1:3.35m for L1, 3.32m for LL; S2:3.05m for L1, 2.66m for LL) and GL (S1:0.49m for L1, 0.46m for LL; S2:0.43m for L1, 0.31m for LL). The plantar peak force decreased in both athletes (S1:1118N for L1, 1043N for LL; S2:1190N for L1, 1136N for LL) while the mean force decreased only in one athlete (S1:416N for L1, 363N for LL; S2: 521N for L1, 525N for LL). The PT increased according to both kinematic and plantar force data (S1:0.35s for L1, 0.37s for LL; S2: 0.31s for L1, 0.34s for LL). The poling data did not show substantial differences between first and last lap. Discussion The high lactate concentration confirmed that the exercise was performed at high intensity, and the decrease of speed between the first and last lap indicated the occurrence of fatigue. The most evident effect on the spatio-temporal parameters is the decrease of both the duration and the distance travelled during the gliding phase. Moreover, the reduction of the peak force and the increment of the propulsion time across laps seems to indicate that fatigue mainly reduce the dynamical characteristic of the legs propulsion. References Zory et al., Human Movement Science 28(2009)85-98